Assessing the Effectiveness of Infection Control Practices in Reducing Hospital-Acquired Infections - Fayz Khalaf Almutairi,; Fahad sager almutairi,; Waleed Mohammed Alruwaili,; Njoud Khalaf Almoutiri,; Abdullah Mabar Yahya Alribhi,; Amro ahya Abdullah Alshablan,; Fayez Ghanam Alharbi,; Awatef Rabee Alanazi,; Shatha Mohammed Saad Al Jumai,; Bashayer Ibrahim Alenaz,; Teflah Hamad Aldawsary, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Hospital-acquired infections (HAIs) are a major global healthcare challenge, contributing to increased morbidity, mortality, and healthcare costs. Despite advancements in infection prevention and control (IPC), these infections remain prevalent, particularly in resource-limited settings. This article explores the burden of HAIs, the role of infection control teams (ICTs), key IPC practices, challenges and barriers to implementation, and actionable recommendations to improve outcomes. Effective IPC relies on evidence-based practices such as hand hygiene, antimicrobial stewardship, environmental cleaning, and adherence to standard precautions. Infection control teams play a pivotal role in developing policies, conducting surveillance, managing outbreaks, and fostering a culture of safety within healthcare facilities. However, barriers such as resource limitations, poor compliance, antimicrobial resistance, and organizational challenges hinder the consistent application of IPC measures. Recommendations to address these issues include strengthening surveillance systems, investing in education and training, enhancing resource availability, promoting antimicrobial stewardship, and leveraging innovative technologies. By addressing these challenges and prioritizing infection control, healthcare facilities can reduce the burden of HAIs, improve patient outcomes, and combat the growing threat of antimicrobial resistance. This comprehensive approach underscores the importance of collaboration, accountability, and sustained commitment to infection prevention efforts globally.